Differential sensitivity of MCPH1- and BRCA2-deficient cancer cells to PARP-1 inhibition - Isobel G. Chapman; Xueqin Wu; Stephany Veuger; Paul A. Jowsey (PLoS ONE, 2026)
Microcephalin-1 (MCPH1) is a tumour suppressor protein that regulates homologous recombination repair (HRR) and is down-regulated in several tumour types. Given that HRR-defective cancer cells can be killed via synthetic lethal approaches, MCPH1 thus represents an attractive target in cancer therapy. Functionally, cells lacking MCPH1 have reported defects in the recruitment and retention of BRCA2 and RAD51 to DNA double strand breaks (DSBs) during HRR, though the magnitude of this defect in human cells is not entirely clear. Multiple studies have demonstrated that HRR-defective cells, particularly those lacking BRCA1 and BRCA2, can be specifically killed by inhibitors of the base excision repair enzyme, poly(ADP-ribose) polymerase-1 (PARP-1). Mechanistically, PARP-1 inhibition can cause (i) elevated DNA single strand breaks (SSBs) and (ii) ‘PARP-1 trapping’ on damaged DNA, both of which can lead to the formation of DSBs during DNA replication, which would normally be repaired by HRR. Given the functional link between MCPH1 and BRCA2, this study aimed to compare HRR-deficiency in cells lacking either protein and correlate this with PARP-1 inhibitor sensitivity. Our data shows that MCPH1-deficient cells are defective in HRR but still retain ~50% activity and this results in little to no sensitivity to two clinically-relevant PARP-1 inhibitors. In contrast, BRCA2-deficient cells showed a far greater defect in HRR and consistent sensitivity to both PARP-1 inhibitors, which was not enhanced by co-depletion of MCPH1. These data suggest that the magnitude of HRR defect in cancer cells influences PARP-1 inhibitor sensitivity and BRCA2 retains significant functionality in the absence of MCPH1.